Assessment of stream flood susceptibility: a cross-analysis between model results and flood losses - Santos, Pedro Pinto (2017)
This study describes a model, which classifies the susceptibility of streams to flooding. Three flood predisposing factors are considered: average slope, accumulated flow, and average relative permeability. Multi-criteria analysis provided results for 11 combinations of weights. Results were compared with the historical record of flood losses reported in newspapers between 1935 and 2010. Lithology appears to function as a relevant factor in differentiating the major sub-basins. Eighty-six percent of flood loss occurrences took place in streams identified by the model. Analysing stream flood susceptibility and flood loss data allow the identification of locations where disaster causes should be searched, apart from those explained by the predisposing factors. The assessment of streams’ flood susceptibility through this methodology is useful in (i) data-rich contexts where additional factors may be considered and the availability of historical records helps to validate the model and (ii) data-poor contexts where data to run the model is easily found.